Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.3 - Adding and Subtracting Rational Expressions with the Same Denominator and Least Common Denominator - Exercise Set: 32



Work Step by Step

$\frac{3x}{4x^{2}+5x+1}$, $\frac{5}{3x^{2}-2x-1}$ 4$x^{2}$+5x+1=4$x^{2}$+x+4x+1=x(4x+1)+1(4x+1)=(x+1)(4x+1) 3$x^{2}$-2x-1=3$x^{2}$+x-3x-1=x(3x+1)-1(3x+1)=(x-1)(3x+1) LCD=(x-1)(x+1)(3x+1)(4x+1)
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.